Marker-assisted forward breeding to develop a drought-, bacterial-leaf-blight-, and blast-resistant rice cultivar - Singh, U.M.; Dixit, S.; Alam, S.; Yadav, S.; Prasanth, V.V.; Singh, A.K.; Venkateshwarlu, C.; Abbai, R.; Vipparla, A.K.; Badri, J.; Ram, T.; Prasad, M.S.; et al. (Wiley, 2022)
Among the different challenges related to rice (Oryza sativa L.) cultivation, drought, bacterial leaf blight (BLB), and blast are the key stresses that significantly affect grain yield (GY) in rice. To ameliorate this issue, marker-assisted forward breeding (MAFB) coupled with a simultaneous crossing approach was used to combine three drought tolerant quantitative trait loci (QTL)—qDTY1.1, qDTY3.1, and qDTY12.1— four BLB genes—Xa4, xa5, xa13, and Xa21—and one blast-resistance gene, Pi9, in the elite rice cultivar Lalat. The introgression lines (ILs) developed in the current study were phenotypically screened for drought, BLB, and blast resistance at the F7– F8 generation. Under the reproductive stage (RS) drought stress, the yield advantage of ILs, with major-effect QTL (qDTY) over elite parent Lalat, ranges from 9 to 124% in DS2019 and from 7 to 175% in WS2019. The selected ILs were highly resistant to BLB, with lesion lengths ranging from 1.3 to 3.0 cm and blast scores ranging from 1 to 3. ILs that were tolerant to RS drought, resistant to BLB, and blast disease and had similar or higher yields than Lalat were analyzed for grain quality. Six ILs were found to have similar grain quality characteristics to Lalat including hulling, milling, head rice recovery (HRR), chalkiness, alkali spreading value (ASV), and amylose content (AC). This study showed that MAFB, together with simultaneous crossing, would be an effective strategy to rapidly combine multiple stresses in rice. The ILs developed in this study could help to ensure yield sustainability in rainfed environments or be used as genetic material in future breeding program